Study of the ionization chamber response to flattening-filter-free photon beams. (February 2017) - Bresolin, A.; Bonfantini, F.; Stucchi, C.G.; Mongioj, V.; Carrara, M.; Pignoli, E.
Abstract: The commissioning of up-to-date linacs, designed to deliver flattening-filter-free (FFF) photon beams, is performed by measurements using air-vented ionization chambers which are often employed for traditional beams. The aim is to select the ionization chambers which are able to minimize the ion recombination effect, critical for these high intensity beams. In order to provide operators with information about the response to FFF beams of widely used chambers, the recombination correction factor k s and the dose-per-pulse (DPP) were determined in different irradiation conditions. The study, performed by using devices available in most radiotherapy departments, confirmed the reliability of the Boag model for FFF beams as well as with-flattening-filter (WFF) beams. The results showed that k s factor largely depends on the spacing between the collecting electrodes ( d el )in the ionization chamber and on the DPP of the linac output, which in turn depends on beam energy but is independent of monitor unit rate (MU/min). For plane-parallel and pin-point chambers, whose d el is minimal, the k s factor is negligible, whereas for Farmer type chambers the recombination could be important and hence the correction is to be applied (also at voltages higher than the recommended one). Highlights: The study confirmed the reliability of Boag model for FFF beams as well as WFF beams. For absolute dosimetry of FFF beams by FC65-P IBA, the k s correction is necessary. k s is independent of monitor unit rate at a given irradiation set-up.